2008
DOI: 10.1002/lt.21482
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of pentoxifylline in hepatopulmonary syndrome

Abstract: Hepatopulmonary syndrome (HPS) results when chronic liver disease or portal hypertension causes intrapulmonary microvascular dilatation with hypoxemia. In experimental HPS, tumor necrosis factor alpha (TNF-␣) overproduction contributes to vasodilatation, which is improved by pentoxifylline, a TNF-␣ inhibitor. The effectiveness of pentoxifylline in humans is unknown. The aim of this open-label, single-arm clinical trial was to assess the efficacy and tolerability of pentoxifylline in patients with cirrhosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 15 publications
0
38
0
1
Order By: Relevance
“…By virtue of its ability to block tumor necrosis factor-a and macrophage-derived NO synthesis, pentoxifylline has garnered attention, as rodent studies suggested potential benefit in experimental HPS (63,64). However, two small studies in patients with HPS reached conflicting conclusions (65,66). Occasionally, patients may present with large pulmonary arteriovenous malformations that are amenable to angiographic embolization, which can at least transiently improve oxygenation (67); however, this is the rare exception.…”
Section: Treatmentmentioning
confidence: 99%
“…By virtue of its ability to block tumor necrosis factor-a and macrophage-derived NO synthesis, pentoxifylline has garnered attention, as rodent studies suggested potential benefit in experimental HPS (63,64). However, two small studies in patients with HPS reached conflicting conclusions (65,66). Occasionally, patients may present with large pulmonary arteriovenous malformations that are amenable to angiographic embolization, which can at least transiently improve oxygenation (67); however, this is the rare exception.…”
Section: Treatmentmentioning
confidence: 99%
“…An open-label, singlearm clinical trial failed to show any improvement in Pa,O 2 or PAa,O 2 after 6 weeks of pentoxifylline. However, the study included only nine patients and not all of them were able to fulfil the intended follow-up or adherence to therapy, mostly due to adverse effects of pentoxifylline [96]. More recently, a blinded randomised crossover study did not show any benefit in PA-a,O 2 after 4 weeks of norfloxacin, as compared with placebo [97].…”
Section: Review: Poph and Hps M Porres-aguilar Et Almentioning
confidence: 99%
“…Agents such as pentoxifylline (a nonspecific phosphodiesterase inhibitor that blocks the synthesis of tumor necrosis factor alpha), methylene blue (an inhibitor of guanylate cyclase), and endothelin B receptor blockers have been tried in a small number of studies with variable results. [12][13][14][15] The treatment of choice for hepatopulmonary syndrome is liver transplantation, with a 5-y survival rate after liver transplantation of 76%. 16 In contrast, the 5-y survival of patients who do not undergo liver transplantation is 23%, with a median survival of 24 months.…”
Section: Discussionmentioning
confidence: 99%